Performance of synchronizing units under reduced system strength - Kuri, Ananya; Höse, Richard; Mehlmann, Gert; Zurowski, Rainer; Audring, Dirk; Luther, Matthias (2021 IEEE PES Innovative Smart Grid Technologies Europe (ISGT Europe), 2021)
In today’s power systems, different trends can be observed, which reduce the total system strength. The result is a weakened reference voltage at the terminals of inverter-based generation. Present-day control systems have been designed under the assumption of a stiff reference voltage. Due to the reduced stiffness, it imposes a challenge for the inverters’ synchronization units. Without a precise synchronization, the entire converter control will become unstable. Therefore, advanced synchronization units are necessary. The performance of selected synchronization units, i.e., the phase locked loop (PLL) and frequency-locked loop (FLL), is analyzed under weak grid conditions. When utilizing the PLL, additional filtering is beneficial to extract the positive-sequence voltage vector. In general, the FLL turns out to be a more robust solution. Furthermore, the dependence of the voltage at the coupling node on the converter and the grid impedance is investigated analytically. In the case of weak grids, the influence of the load on the node voltage must be considered. Thus, a novel impedance ratio is introduced to assess the system strength under weak grid conditions. <br
Keywords: FLL; PLL; SCR; Synchronization; System strength; Weak grids